Magnesium AZ63 Alloy Protective Coatings by Plasma Electrolytic Oxidation in Mixed Aqueous Electrolytes - Patrascu, Ion; Negrea, Aurelian Denis; Malinovschi, Viorel; Lungu, Cristian Petrica; Cimpoesu, Ramona; Ducu, Marian Catalin; Schiopu, Adriana-Gabriela; Moga, Sorin Georgian (Engineering, Technology & Applied Science Research, 2024)
Ceramic protective coatings, primarily composed of spinel (MgAl2O4), magnesia (MgO), and trimagnesium phosphate (Mg3(PO4)2), were produced on magnesium AZ63 alloy through Plasma Electrolytic Oxidation (PEO) in mixed sodium phosphate/aluminate electrolytes with varying aluminate concentrations and constant processing time. The morpho-structural and compositional characteristics of the coatings were studied using X-ray diffraction, scanning electron microscopy, and energy-dispersive X-ray spectroscopy. Their functional mechanical and anti-corrosive properties were assessed through tribological testing, electrochemical impedance spectroscopy, and potentiodynamic bias tests. The findings indicated that the samples processed through PEO exhibited significantly enhanced properties compared to the AZ63 magnesium alloy. The best tribological properties were observed for the lowest aluminate concentration. Optimum corrosion resistance properties were obtained for coatings produced in a mixed electrolyte of 10 g/L sodium phosphate and 20 g/L sodium aluminate.